2020
DOI: 10.1097/qco.0000000000000672
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance in Salmonella Typhi: implications for South Asia and travel

Abstract: Purpose of review Recent attempts at mapping Typhoid epidemiology have revealed an enormous burden of disease in developing countries. Countries hitherto believed to have a low incidence, such as the African subcontinent, on accurate mapping were found to have a significant burden of disease. Drug resistance, because of rampant overuse of antibiotics, has driven selection pressure to extensively drug-resistant typhoid becoming a reality in the Indian subcontinent. With widespread travel, importatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…However, a decline in MDR strains of EF has been demonstrated in India and Bangladesh; nevertheless, fluoroquinolone resistance patterns were steadily increasing. In contrast, there is a preponderance of MDR strains in Pakistan and Nepal and evolving extensively drug-resistant (XDR) strains in Pakistan [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a decline in MDR strains of EF has been demonstrated in India and Bangladesh; nevertheless, fluoroquinolone resistance patterns were steadily increasing. In contrast, there is a preponderance of MDR strains in Pakistan and Nepal and evolving extensively drug-resistant (XDR) strains in Pakistan [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies point to the lack of access to healthcare services along with the increased supply of over-the-counter (OTC) drugs as one of the main contributors to antibiotic resistance in lower-middle-income countries [ 5 ]. In 2016, extensively drug-resistant Salmonella Typhi was isolated in Pakistan and has been responsible for multiple outbreaks in Pakistan and many travel-related cases all over the world [ 6 ]. In this study, we have observed the rate of resistance and sensitivity of various antibiotics in the case of Salmonella Typhi.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, healthcare professionals have witnessed the rapid rise of multi-drug resistant (MDR) and extensive drug-resistant (XDR) Salmonella enterica serotype Typhi [ 5 ][ 6 ]. Typhoid fever that is resistant to traditional first-line antibiotics including ampicillin, chloramphenicol, and trimethoprim-sulfamethoxazole is regarded as MDR typhoid [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various resistance mechanisms make many Salmonella Typhi bacteria fall into the category of Multi-Drug Resistant (MDR), resistant to antibiotics like ampicillin, chloramphenicol, and cotrimoxazole. Some even reach the Extensively Drug-Resistant (XDR) category, showing resistance to fluoroquinolone and third-generation cephalosporin antibiotics [12]. These findings highlight the highly complex and potent resistance capabilities of Salmonella Typhi against various antibacterial agents.…”
Section: Antibacterial Activity Test Using the Diffusion Methodsmentioning
confidence: 99%
“…Globally, Salmonella Typhi has shown resistance to Ampicillin, Chloramphenicol, Trimethoprimsulfamethoxazole, Nalixylic Acid, Ciprofloxacin, Ceftriaxone, and Azithromycin [11]. This bacterium has even shown multi-drug resistance (MDR) in South Asian countries, namely India, Pakistan, and Bangladesh [12].…”
Section: Introductionmentioning
confidence: 99%